Arctic FROST Young Scholars Panel – Arctic anthropology and sustainability - Alexander Meitz (Department of Social and Cultural Anthropology, Faculty of Social Sciences, University of Vienna); Susanna Gartler (Department of Social and Cultural Anthropology, Faculty of Social Sciences, University of Vienna) (The Polar Journal, 2017)
The abstract is available here: https://uscholar.univie.ac.at/o:724032 The abstract is available here: https://uscholar.univie.ac.at/o:724032